Addressing long-acting reversible contraception access, bias, and coercion: supporting adolescent and young adult reproductive autonomy. Issue 4 (August 2021) - Bryson, Amanda; Koyama, Atsuko; Hassan, Areej
Abstract : Purpose of review: Long-acting reversible contraception (LARC) is comprised of highly effective methods (the subdermal implant and intrauterine devices) available to adolescents and young adults (AYAs). Professional medical societies endorse LARC use in AYAs and, more recently, have emphasized the importance of using a reproductive justice framework when providing LARC. This article reviews reproductive justice, discusses contraceptive coercion, examines bias, and highlights interventions that promote equitable reproductive healthcare. Recent findings: Research indicates that both bias and patient characteristics influence provider LARC practices. AYA access to comprehensive LARC services is limited, as counseling, provision, management, and removal are not offered at all sites providing reproductive healthcare to AYAs. Interventions aimed at addressing provider bias and knowledge, clinic policies, confidentiality concerns, insurance reimbursement, and systems of oppression can improve AYA access to equitable, comprehensive contraceptive care. Additionally, the COVID-19 pandemic has exacerbated inequities in reproductive healthcare, as well as provided unique innovations to decrease barriers, including telemedicine LARC services. Summary: Clinicians who care for AYAs should honor reproductive autonomy by approaching contraceptive services with a reproductive justice lens. This includes implementing patient-centered contraceptive counseling, increasing access to LARC, eliminating barriers to LARC removal, and committing to systemic changes to address healthcare inequities.